(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines morphological innovations in contemporary Russian that reflect ongoing processes of linguistic evolution at the turn of the 21st century. The study focuses on the tendencies toward analyticism, the borrowing and adaptation of foreign morphemes, the activation of clipping processes, the emergence of hybrid word-formation models, and the impact of digital communication on the morphological system. Based on corpus and functional-semantic analyses, the author concludes that Russian morphology is undergoing an active restructuring phase, combining traditional synthetic features with the formation of new analytical-hybrid models